2023
DOI: 10.1097/hcr.0000000000000795
|View full text |Cite
|
Sign up to set email alerts
|

Proportional Internal Work—a New Parameter of Exercise Testing in Study of Health in Pomerania (SHIP)

Abstract: Purpose: Cardiopulmonary exercise testing usually requires a maximal exhaustive effort by the patient and is time consuming. The purpose of this study was to assess whether the cost to initiate exercise termed “proportional internal work” (PIW) was related to cardiovascular disease (CVD) risk factors, ventilatory parameters, and mortality. Methods: We used data from population-based Study of Health in Pomerania. A total of 2829 (49.5% female) study part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In our study we showed that patients have a similar PIW compared to healthy individuals from the general population. In 580 patients as well as in 354 SHIP controls the PIW was between 14 and 15%, which correspondents well with the PIW of 14.7%, which we previously reported for the whole SHIP-cohort 14 . While the PIW did only differ slightly between the patients and the SHIP controls, the PIW (Watt) was significantly higher in the patients than in the SHIP controls (18.0% vs. 15.9%).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In our study we showed that patients have a similar PIW compared to healthy individuals from the general population. In 580 patients as well as in 354 SHIP controls the PIW was between 14 and 15%, which correspondents well with the PIW of 14.7%, which we previously reported for the whole SHIP-cohort 14 . While the PIW did only differ slightly between the patients and the SHIP controls, the PIW (Watt) was significantly higher in the patients than in the SHIP controls (18.0% vs. 15.9%).…”
Section: Discussionsupporting
confidence: 89%
“…This indicates that the PIW may be a useful screening parameter in healthy individuals independent of the CPET protocol. In a previous analysis based on SHIP data, we demonstrated that a higher PIW was associated with a higher risk to die 14 . Future studies are needed to reveal, whether the PIW adds predictive value independent of established cardiovascular risk factors such as age, sex, BMI, blood pressure, diabetes or dyslipidaemia.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations